Heterogeneity in past-year smoking, current tobacco use, and smoking cessation behaviors among light and/or non-daily smokers - Toluwa Omole; Timothy McNeel; Kelvin Choi (Tobacco Induced Diseases, 2020)
Introduction Prevalence of light daily smoking, 10 CPD) and frequency (non-daily vs daily). Combinations of T0 and T1 smoking behaviors resulted in 15 smoking trajectories ending in light/non-daily smoking and a 16th category of heavy daily smokers at T1. Differences in demographics, tobacco use, and smoking cessation behaviors were assessed by using weighted multivariable regression models.